Pengaruh Fasilitas Terhadap Kepuasan Pengunjung di Kiara Artha Park Bandung - Arif Ariagus Dwi Fajar; Gilang Pratama Putra; Neni Rohaeni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The problem addressed in this thesis is the influence of facilities on visitor satisfaction at Kiara Artha Park Bandung. The purpose of this research is to identify the facilities and visitor satisfaction at Kiara Artha Park Bandung. The research method used is a quantitative approach with a descriptive approach. Data collection was conducted by distributing Likert scales to respondents who have visited and experienced Kiara Artha Park Bandung. The sampling technique employed is random sampling, with a research sample consisting of 100 respondents selected randomly. Data analysis was carried out using descriptive analysis to measure the influence of facility variables on visitor satisfaction. The results of the study indicate that facilities have a positive and significant impact on visitor satisfaction. The most influential facilities include cleanliness, comfort, and the completeness of public facilities. Based on these findings, it is recommended that the management of Kiara Artha Park continues to improve the quality and availability of facilities to enhance visitor satisfaction and the park's appeal as a tourist destination.